Inocybe messapica (Inocybaceae, Agaricales, Basidiomycota), a new species in section Splendentes, from Mediterranean oak woods - Cervini, Mario (Phytotaxa, 2021)
Inocybe messapica sp. nov., collected in Apulia (Italy) under Quercus coccifera and Quercus ilex, is presented with description, colour photographs, and line-drawings of the microscopic features. This species is proposed as new based on both morphology and molecular phylogenetic analysis. It is characterized by the stout habit, a dark castaneous brown pileus covered with a whitish velipellis, a non-marginate bulbous stipe base, and smooth amygdaliform spores. A comparison of I. messapica with I. athenana and similar species is also provided.